(untitled) (AKURAT | Jurnal Ilmiah Akuntansi FE UNIBBA, 2021)
This study aims to examine the effect of understanding taxation, love of money, and religiosity on the desire to commit tax evasion in students of the Accounting Study Program Faculty of Economics Universitas Sarjanawiyata Tamansiswa. This research method uses descriptive quantitative statistical methods and uses primary data by using a questionnaire. The sampling technique used snowball sampling technique. The data collection technique used a questionnaire via google form which was distributed to students of the Accounting Study Program Faculty of Economics Universitas Sarjanawiyata Tamansiswa class 2017, class 2018, and class 2019. The samples used in this study were 100 samples. Analysis of the data used is multiple regression analysis which is processed using the IBM SPSS version 20 program. The results of this study indicate that the understanding of taxation has a negative effect on the desire to commit tax evasion. Love of money has no effect on the desire to commit tax evasion. Religiosity has a negative effect on the desire to commit tax evasion